Insect-habitat-plant interaction networks provide guidelines to mitigate the risk of transmission of Xylella fastidiosa to grapevine in Southern France - Xavier Mesmin; Marguerite Chartois; Pauline Farigoule; Christian Burban; Jean-Claude Streito; Jean-Marc Thuillier; Éric Pierre; Maxime Lambert; Yannick Mellerin; Olivier Bonnard; Inge van Halder; Guillaume Fried; et al. (PLoS ONE, 2025)
Xylella fastidiosa ( Xf ) is a xylem-limited bacterium that has been recorded in several European countries since its detection in 2013 in Apulia (Italy). Given the prominence of the wine industry in many southern European countries, a big threat is the development of Pierce’s disease in grapevines. Yet, the insect-habitat and insect-plant interaction networks in which xylem feeders, possible vectors of Xf , are involved around European vineyards are largely unknown. Here we describe these networks in three key wine-growing regions of southern France (Provence-Alpes-Côte d’Azur, Occitanie, Nouvelle-Aquitaine) to identify primary xylem feeder habitats, and assess their specialization degree at the habitat, plant family, and plant species levels. A total of 92 landscapes (and 700 sites) were studied over three sampling sessions in the fall 2020, spring 2021, and fall 2021. Among the habitats sampled, meadows hosted the largest xylem feeder communities, followed by alfalfa fields. Vineyard headlands and inter-rows hosted slightly smaller xylem feeder communities, indicating that potential Xf vectors thrive near crops. Grapevines hosted few xylem feeders, suggesting rare but possible transfer to vulnerable crops. Philaenus spumarius , Aphrophora alni , Lepyronia coleoptrata , and Cicadella viridis were all similarly generalists at the habitat, plant family or plant species level. The only specialist was Aphrophora grp. salicina , which was restricted to riparian forests and to Salicaceae. Neophilaenus spp. were extremely specialist at the plant family level (Poaceae), but rather generalist at the habitat and plant species levels. All 1017 insects screened for the presence of Xf tested negative, showing that Xf is not widespread in the studied regions. Our study provides new basic ecological information on potential vectors of Xf , especially on their specialization and feeding preferences, as well as practical information that may be relevant for the design of epidemiological surveillance plans.